The Effect of the COVID-19 Pandemic on Maxillofacial Trauma treated in a Hospital Emergency Room: a Comparative Study - da Silva, Raul Santos; Benassi, Camila Maciel; da Silva, Tainá Belline; Palmieri Junior, Celso Fernando; Cerqueira Luz, João Gualberto de (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Background: The COVID-19 pandemic has greatly impacted medical and surgical activities, and a decline in maxillofacial trauma incidence was noticed during the lockdown period. Objective: To evaluate the effects of the COVID-19 pandemic on the incidence of maxillofacial trauma in patients treated in a level I trauma center hospital. Methods: Data from patients seen between January and December 2019 (the pre-pandemic group), and during the same period in 2020 (the pandemic group), were analyzed. Personal data, causes and types of maxillofacial trauma sustained were extracted and statistically compared (p<0.050). Results: There were 1034 patients in the pre-pandemic group and 890 patients in the pandemic group. There was an increase in the number of motor vehicle accidents and a decrease in the number of sports accidents (p<0.001) in the pandemic group. The pandemic group exhibited a decrease in the number of patients with maxillofacial fractures, and dentoalveolar trauma, and an increase in the number of soft tissue injuries (p<0.001). Compared with those of other studies, our results confirmed a decrease in the number of maxillofacial trauma patients, with variations in personal data for various reasons. Conclusion: There was a decrease in the incidence of maxillofacial fractures and dentoalveolar trauma and an increase in the incidence of soft tissue injuries, with variations in the types of these traumas, indicating the possible influence of differences in the causal factors during the pandemic.